Radical scavenging and anti-acetylcholinesterase activities of aqueous extract of wild pistachio (Pistacia atlantica Desf.) leaves - Peksel, Aysegul; Arisan, Inci; Yanardag, Refiye (KOREAN SOCIETY FOOD SCIENCE & TECHNOLOGY-KOSFOST, 2013)
The purpose of this work is to assess the radical scavenging activity, acetylcholinesterase inhibition, and proline content of an aqueous extract from wild pistachio (Pistacia atlantica Desf.) leaves. The effect of aqueous extract on superoxide radical scavenging, hydroxyl radical scavenging, N,N-dimethyl-1,4-phenylendiammoniumdichloride (DMPD center dot+) radical scavenging, ABTS(center dot+) radical scavenging, nitric oxide scavenging, and beta-carotene bleaching activities was examined. This study found that the aqueous extract possesses considerable amounts of flavonoids (33.52 +/- 2.04 mu g catechin equivalents/mg of extract). The effect of this extract in scavenging activity of hydroxyl radical and DMPD center dot+ was significantly better than that of ascorbic acid and butylated hydroxyanisole (BHA). The effect of the extract in superoxide and ABTS(center dot+) was significantly similar than that of tested standard antioxidants. The proline content of the extract was found to be 0.54 +/- 0.01 mu g proline/mg of extract. Aqueous extract of P. atlantica inhibited acetylcholinesterase activity effectively with IC50 value of 58.05 +/- 0.12 mu g/mL.
Keywords: Pistacia atlantica Desf.; antioxidant activity; radical scavenging ability; proline content; antiacetylcholinesterase activity; IN-VITRO; MEDICINAL-PLANTS; AMINO-ACIDS; ACETYLCHOLINESTERASE; L.; POPULATION; LENTISCUS; OILS; Food Science & Technology